A taxonomic review of the genus Clitostethus Weise (Coleoptera: Coccinellidae), with descriptions of two new species from China - Xie, Xiu-Feng; Wang, Xing-Min; Peng, Zheng-Qiang; Chen, Xiao-Sheng (Zootaxa, 2026)
Nine species of the genus Clitostethus Weise, 1885 are revised, including the description of two new species: Clitostethus conensis Xie, Wang & Chen, sp. nov. and Clitostethus tongbiguanus Xie, Wang & Chen, sp. nov. Clitostethus luteoniger (Canepari, 1997) is recorded from China for the first time. A key to the Chinese species is provided. Nomenclatural history, diagnoses, detailed descriptions, illustrations, and distribution data for each species are presented. A catalogue of all known species in this genus is also included.